PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, BUDAYA ORGANISASI DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DALAM PELAPORAN PENDAPATAN UNTUK PAJAK HOTEL - Ni Kadek Mita Santini; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
This study aims to analyze the effect of Internal Control Effectiveness, Organizational Culture and Compliance to Accounting Rules on the Tendency of Accounting Fraud in Reporting Income for Hotel Taxes . The population in this study is a employee of accounting department in three-star hotel taxpayer in the Kuta District area. The sample of this study amounted to 68 people who are hotel employees who have served for more than one year as the Head of Accounting and Staff of the Revenue Section because these sections are directly involved in reporting income for hotel taxes. The sampling technique used was purposive sampling technique. The results of this study indicate that the effectiveness of internal control and organizational culture does not significantly influence the tendency of fraud in reporting revenue for hotel taxes. Meanwhile, Compliance to accounting rules has a negative and significant effect on the tendency of fraud in reporting revenue for hotel taxes.